Re-imagining citizenship education : empowering students to become critical leaders and community role models - Ramirez, Pablo C. (Emerald Publishing Limited : Information Age Pub., 2023)
"Global migration and increasing diversity within nations are challenging conceptions of citizenship all over the world. The percentage of ethnic minorities in nation- states throughout the world has increased significantly within the past 30 years. The United States Census, for example, projects that 50% of the population will consist of culturally, linguistically, racially, ethnic, and religiously diverse groups by 2050. With an increase growth of diversity within national borders, issues concerning educational equity, equality, and civic engagement have not always been well attended to in educational and societal contexts. Growing ethnic diversity in schools/ society has not automatically led to a dismantling of persistent educational barriers or structural inequalities. In the past decade, culturally, ethnically, and linguistically diverse populations have faced barriers impacting their rights as citizens in the United States and international contexts. Citizenship and the rights that are associated with being a citizen are re- framed when culturally, ethnically, and linguistically students seek equality. In 2020, many urban cities in the United States witnessed Latino/ Black youth demonstrate peacefully guided by social justice and their civic responsibilities. Similarly, in international contexts students have demonstrated civil disobedience by expressing concerns about their rights as citizens and the disempowerment of communities. In this special edition, we call attention to the role of Critical Multicultural Citizenship Education (CMCE) in schools, societies and global contexts. The fundamental goal of CMCE is to increase not only the students' awareness of, and participation in, the political aspects of democracy, but also students' abilities to create and live in an ethnically diverse and just community. CMCE challenges and transforms existing ways in which students engage civically and democratically in local, national, and global contexts. We use and are guided by Freire's (2007) notions of critical consciousness in discussing CMCE. Within CMCE, students are able to name issues impacting their lives and begin to reflect on ways to improve communities and societies. Further, CMCE emphasizes critical activism that centers on transforming institutional barriers. Youth are able to develop critical citizenship thinking/ skills in order to enact agency in local, community and global contexts . Teachers that use CMCE have a significant role and are essential in creating an optimal learning environment where students can develop skills to critique and challenge oppression in local, community and global contexts.We believe that teachers are essential in this process and argue that the dialectical process between teachers and students is key to reframing citizenship. A range of empirical studies have drawn from a CMCE framework to document the way teachers , students and communities interpret citizenship to seek equality in schools, classrooms and communities. This volume will add and expand on CMCE. The special edition addresses major issues associated with the active citizenship of diverse youth in schools and communities. This volume names issues impacting Latino/a, Black, immigrant and refugees in the U.S. and other contexts. We emphatically believe that students in K-12 settings must begin to understand their rights as citizens and also advocate for the rights of others in order for communities in the U.S. and international contexts to achieve democracy. The articles are organized in to three sections"--